Implementasi Pendampingan Pelaporan Administrasi Keuangan Pemerintahan Desa Sukahening - Sugianto, Iwan (CV. SINAR HOWUHOWU, 2025)
Assistance in the financial reporting of village administration is a strategic effort to enhance the capacity and accountability of village governments in managing finances transparently and in accordance with regulations. This study aims to identify the effectiveness of implementing financial reporting assistance for village officials, particularly through the use of the Village Financial System application (Sistem Keuangan Desa or SISKEUDES). A participatory approach was employed, using observation, interviews, and document review methods to compare financial reporting practices before and after the implementation of assistance. The results show a significant improvement in the technical capabilities of village officials, timeliness in financial report submissions, and better organization of administrative documents. Furthermore, the program encouraged public transparency by publishing summary reports to the community. Existing challenges include limited human resources and the need for continuous training. Therefore, financial reporting assistance has proven to be a relevant and effective intervention in strengthening good village financial governance.